The Accountability of Reporting Covid-19 Management Funds in Pangkalpinang City (The Theory of Planned Behavior Approach) - Rahmanisa Rahmanisa; Supri Supri; Dirga Ferdian; Sumiyati Sumiyati (Jurnal Profita: Komunikasi Ilmiah Akuntansi dan Perpajakan, 2023)
Covid-19's outspread made the government implement a reallocation policy for Covid-19 funds so that this research was conducted to see the accountability of local governments in reporting Covid-19 management funds based on the Theory of Planned Behavior. The use of primary data was taken from the distribution of questionnaires at the Pangkalpinang City Local Government Finance Office. Where the criteria for the sample is the employees in the fields involved in reporting Covid-19 management funds. The study uses a quantitative approach with the testing of double linear regression analysis. The study has shown that attitudes toward behaviour, subjective norms and self-efficacy affect simultaneous and significantly on the variable of intentions to act accountable. While partial effects are both significant and positive indicated only by the variable of self-efficacy on intentions to act accountable. The attitude toward behavior and subjective norms has shown that there is no significant effect on the variable of intentions to act accountable. The three independent variables have an influence of 17.1% in explaining the intention to act accountable and the remaining 82.9% is explained outside of these three variables.